Taymāʼ I : archaeological exploration, palaeoenvironment, cultural contacts - Hausleiter, Arnulf,; Eichmann, Ricardo,; al-Najem, Muhammad,; Bagg, Ariel M., (Taymāʼ. Multidisciplinary series on the results of the Saudi-German Archaeological Project., 2018)
This is the first of a series of books reporting on a Saudi-German archaeological project at at Taymāʼ: the current archaeological exploration of the oasis is contextualised with previous and ongoing research within the region, while offering a first overview of the settlement history of the site, possibly starting more than 6000 years ago.